POLIMORFISMO DO GENE DA ENZIMA CONVERSORA DE ANGIOTENSINA EM INDIVÍDUOS HIPERTENSOS DO SUL DO BRASIL - Alonso, Kátia Cristina (2012)
The arterial hypertension is characterized as a multifactorial disorder, influenced by genetic and environmental factors. Environmental factors are most responsible for the accelerated growth of this disease. The physical exercise is considered a very important non pharmacological model of treatment for the hypertension. Actually, how much genes are studying for better clarified the real relationship between the genetic and blood pressure (BP) control. The insertion/deletion (I/D) The arterial hypertension is characterized as a multifactorial disorder, influenced by genetic and environmental factors. Environmental factors are most responsible for the accelerated growth of this disease. The physical exercise is considered a very important non pharmacological model of treatment for the hypertension. Actually, how much genes are studying for better clarified the real relationship between the genetic and blood pressure (BP) control. The insertion/deletion (I/D) polymorphism, with 287 base pairs at the intron 16, of the angiotensin-converting enzyme (ACE) gene has recently been related with HBP in different populations. Therefore, the aim of the present study was to investigate possible association of the polymorphism of the ACE forward clinical diagnosis of hypertension in a sample population from southern Brazil, submitted to physical training and / or drug treatment. Thus, it was possible to evaluate and verify a positive effect on BP control, under the influence of aerobic exercise short-term (two months) in 10 hypertensive individuals heterozygous for ACE (genotype ID). Furthermore, we evaluated the possible relationship between the polymorphism insertion/deletion (I/D) with hypertension in a group consisting of 78 hypertensive individuals, and these showed no direct relationship with the disease. The groups were not showed genetic structure and the genotypic classes presented out of equilibrium of Hardy-Weinberg. The D allele was minor frequent, and new alleles was descript. It is suggest that other mechanisms post-transcriptions are linked in the gene regulation and ECA function.polymorphism, with 287 base pairs at the intron 16, of the angiotensin-converting enzyme (ACE) gene has recently been related with HBP in different populations. Therefore, the aim of the present study was to investigate possible association of the polymorphism of the ACE forward clinical diagnosis of hypertension in a sample population from southern Brazil, submitted to physical training and / or drug treatment. Thus, it was possible to evaluate and verify a positive effect on BP control, under the influence of aerobic exercise short-term (two months) in 10 hypertensive individuals heterozygous for ACE (genotype ID). Furthermore, we evaluated the possible relationship between the polymorphism insertion/deletion (I/D) with hypertension in a group consisting of 78 hypertensive individuals, and these showed no direct relationship with the disease. The groups were not showed genetic structure and the genotypic classes presented out of equilibrium of Hardy-Weinberg. The D allele was minor frequent, and new alleles was descript. It is suggest that other mechanisms post-transcriptions are linked in the gene regulation and ECA function.